Analisis Pengaruh Gaya Kepemimpinan Dan Partisipasi Masyarakat Terhadap Kualitas Pelayanan Publik Yang Dimediasi Oleh Kinerja Aparatur Dinas Kesehatan Kabupaten Pamekasan - Dwi Kurnia Putri; Esa Wahyu Endarti (Journal of Management and Creative Business, 2024)
This type of research is explanatory research, the research approach uses a quantitative approach, the research sample is 51 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To find out the description of leadership style, community participation, apparatus performance and quality of public services Pamekasan District Health Office; 2). To find out and analyze whether leadership style has an influence on the quality of public services at the Pamekasan District Health Office; 3). To find out and analyze whether leadership style has an influence on the performance of apparatus at the Pamekasan District Health Office; 4). To find out and analyze whether community participation has an influence on the quality of public services at the Pamekasan District Health Office; 5). To find out and analyze whether community participation has an influence on the performance of apparatus at the Pamekasan District Health Office; 6). To find out and analyze whether the performance of the apparatus has an influence on the quality of public services at the Pamekasan District Health Office; 7). To find out and analyze whether leadership style has an indirect effect on the quality of public services mediated by the performance of the Pamekasan District Health Office; 8). To find out and analyze whether community participation has an indirect influence on the quality of public services which is mediated by the performance of the Pamekasan District Health Office apparatus.The results of the study show that: 1) Leadership style has a positive and significant effect on the quality of public services as evidenced by the value of the Original Sample which is equal to 0.306; 2). Leadership style has a positive and significant effect on apparatus performance as evidenced by the value of the Original Sample that is equal to 0.477. 3). Work discipline has a positive and significant effect on motivation as evidenced by the value of the Original Sample which is equal to 0.438; 4). Community participation on apparatus performance has a positive and significant effect as evidenced by the value of the Original Sample that is equal to 0.398; 5). Apparatus performance on the quality of public service has a positive and significant effect as evidenced by the value of the Original Sample that is equal to 0.601; 6). Leadership style on the quality of public services mediated by apparatus performance has a positive and significant effect as evidenced by the value of the Original Sample that is equal to 0.287; 7). Community participation in the quality of public services mediated by the performance of apparatus has a significant positive effect as evidenced by the value of the Original Sample which is equal to 0.239